What's age got to do with it? A primer and review of the workplace aging literature. Issue 4 (19th October 2022) - Beier, Margaret E.; Kanfer, Ruth; Kooij, Dorien T. A. M.; Truxillo, Donald M.
Abstract: As populations in the United States and around the world continue to age, it has become increasingly important to understand how organizations can create working conditions that attract, support, and retain workers across the lifespan. In this paper, we provide a primer on current theory and research on age in the workplace. We briefly describe lifespan theories that have guided recent advances in the field, discuss the implications of these theories for an aging workforce, and provide an overview of current research streams that address the work and nonwork factors affecting performance, well‐being, and workforce participation among mature workers. Based on this review, we provide recommendations for future research and practice.